Gambaran Indeks Aterogenik Plasma Pada Penderita Diabetes Melitus - Sunaidi, Yanti; Sulfiani; Sefhia Purnama Dita; Muhammad Ihza Lisan Shidqi; Eleventi Oktarina Putri; Antoni Aldo Danendra Sawal (Jurnal Analis Kesehatan Kendari, 2025)
Diabetes mellitus is a group of metabolic disorders characterized by elevated blood glucose levels due to abnormalities in insulin secretion or insulin resistance. This condition increases the risk of cardiovascular disease by triggering dyslipidemia, which is marked by elevated cholesterol, increased levels of low-density lipoprotein (LDL), increased triglycerides, and decreased high-density lipoprotein (HDL) in the blood. Dyslipidemia in diabetic patients is associated with a higher Atherogenic Index of Plasma (AIP), which plays a role in the development of atherosclerosis, a key factor in cardiovascular disease. The logarithmic ratio of triglycerides to HDL can be used to determine the AIP, which serves as a marker for assessing atherogenicity and the risk of cardiovascular disease. This study aimed to predict cardiovascular disease in patients with diabetes mellitus through the evaluation of AIP values. The research was descriptive, involving 32 subjects selected using purposive sampling, and conducted at Dr. Tadjuddin Chalid General Hospital, Makassar, South Sulawesi. Based on the results of 32 subjects: 0 subjects (0%) were categorized as having low cardiovascular risk AIP, with an average value of 0; 1 subject (3%) was in the moderate risk category, with an average AIP of 0.19; 31 subjects (97%) were in the high cardiovascular risk category, with an average AIP of 0.82. These findings indicate that most diabetic patients tend to have a high-risk cardiovascular disease, compared to moderate or low-risk categories.